Analysis of Protein Levels of Fermented Sarden Fish Pempek - Yani, Ade Vera; Idealistuti; Savitri, Dewi; Sebayang, Nico Syahputra (Indonesian Journal of Agricultural Research, 2022)
Research on the topic â€œconducted to find out the chemical characteristics of fermented sardine lenjer pempekâ€. Using a Randomized Block Design (RAK) which was arranged in a non-factorial manner with a comparison of the length of fermentation time consisting of 4 treatments and repeated 5 (five) times. Chemical parameters observed in this research is analysis protein, The tests carried out on pempek lenjer were compared with the length of fermentation time P0 (without fermentation/control), P1 (fermentation time 12hours), P2 (fermentation time 24 hours), P3 (36 hours of fermentation time). The results of the F test on chemical analysis were followed by Dunnet test. Observation parameters are chemical analysis of protein. The results showed P0: 6.86 %, P1: 7.44 %, P2: 7.86 %, the highest protein content with a value of P3: 9.03 %.